THE IMPACT OF ENVIRONMENTAL MANAGEMENT ACCOUNTING, GREEN INVESTMENT, AND ESG DISCLOSURE ON FIRM VALUE: AN EMPIRICAL STUDY OF THE ENERGY SECTOR ON THE INDONESIA STOCK EXCHANGE 2020-2024 PERIOD - Disya Yuke Farhana; Mukhzarudfa; Ratih Kusumastuti; Wiwik Tiswiyanti (PT. ZILLZELL MEDIA PRIMA, 2026)
This study examines the impact of Environmental Management Accounting (EMA), Green Investment (GI), and ESG Disclosure on firm value (Tobin's Q) among 16 energy sector companies listed on the Indonesia Stock Exchange (IDX) from 2020-2024. Using a quantitative approach and multiple linear regression, the study analyzed 80 observations selected through purposive sampling. The results indicate that the model significantly explains 66.4% of the variation in firm value (Adjusted R² = 0.664). In partial analysis, only EMA was found to have a significant positive effect on firm value (β = 0.997; t = 12.482; p < 0.001). Conversely, Green Investment (β = 0.128; t = 1.506; p = 0.136) and ESG Disclosure (β = -0.022; t = -0.632; p = 0.529) showed no significant impact. These findings suggest that the systematic internalization of environmental costs through EMA is a key driver of market perception in Indonesia's energy sector. Consequently, firms and regulators should prioritize the depth of internal environmental management practices over mere formal disclosure to effectively enhance investor confidence and corporate value.